Early Childhood Teachers’ Understanding of Sex Education: A Descriptive Survey in Bandung - Hikmah Nuzulunnisa; Susan Maulani; Agus Ruswandi (CV. AFDIFAL MAJU BERKAH, 2026)
This study aims to analyze early childhood education (ECE) teachers’ understanding of sex education by examining three key indicators: fundamental knowledge, attitudes, and the readiness of instructional media and learning materials. Using a quantitative descriptive approach, data were collected from ECE teachers via structured questionnaires and subsequently analyzed using descriptive statistics. Data were collected from 57 early childhood teachers in Bandung using a total sampling technique. The findings show that teachers’ overall understanding of sex education falls into the moderate category. In terms of fundamental knowledge, 96% of teachers demonstrated a high level of conceptual understanding, with a mean score of 42.28 out of 45, indicating strong awareness of body safety and privacy principles. Teachers also exhibited positive attitudes toward implementing sex education, with 65% categorized as high and 30% as moderate. However, the study reveals significant challenges in the readiness of instructional media, with 53% of teachers in the moderate category and 23% in the low category due to limited access to appropriate storybooks, visual aids, and educational videos. The study concludes that although teachers possess strong conceptual knowledge and supportive attitudes, the lack of adequate learning materials hinders optimal implementation. Strengthening institutional support and providing developmentally appropriate media are essential to improving sex education practices in ECE settings